Mendorong Sistem Jaminan Kesehatan Nasional Baru di Indonesia; Belajar dari Pengalaman Australia - Sujai, Mahpud (Badan kebijakan Fiskal, 2013)
Significant change of Indonesian economy has lead to the need of people more than just basic need such as food and clothes. Others such as health and education have become a must for Indonesian. Anticipating this condition, government will implement new universal coverage health system in 2014 as mandated by law. This paper has objectives to explore several aspects which contribute or influence to the policy formulation and implementation, particularly in designing new health insurance system in Indonesia and learning from Australian experience and best practice. Methodology used in this paper is both primary research such as in depth interview with some health economist, expert form universities, government researcher as well as observation to the organization that manage health system in Australia and secondary research by doing literature review of health insurance system, benchmarking, compare and contrast the health insurance system in Indonesia and Australia and analyze the best and suitable ones for implemented in the future. There are several interesting findings that can be recommended such as Australian health reform and relationship between public and private health system.